An Epigenetic Prism to Norms and Values - Hendrickx, Kim; Van Hoyweghen, Ine (Frontiers in Genetics, 2018)
In this article, we ask to what extent the specific characteristics of epigenetics may affect the type of questions one can ask about human society. We pay particular attention to the way epigenetic research stirs debate about normative and moral issues. Are these issues implied by scientific evidence as an outcome of research? Or do moral and normative issues also shape how research is done and which problems it addresses? We briefly explore these questions through examples and discussions in (social-) scientific literature. In the final section, we propose an additional dimension and a refocusing of attention from issues of scientific evidence alone (asking what kind of evidence epigenetics produces and how it does so) to a broader picture on epigenetics as a mode of attention that encourages relational and process-oriented thinking with entities, values and scales that may not yet fit within conventional problem-frames that inform research funding and policy-making. We argue that the task of (post-)ELSI approaches is to take inspiration from the ecological complexity of epigenetics in order to bring more relations, relief and gradient in our ethical and political questions.